(untitled) (Journal Of Educational and Psychological Researches, 2022)
The current research aims to identify the extent to which cognitive economics skills are included in the content of the chemistry textbook for the third intermediate grade, and the research sample was represented in the chemistry textbook for the third intermediate grade. A list of knowledge economy skills was prepared (6) main skills (basic skills, communication skills, thinking skills, work skills Group, information-gathering skill, behavioral skills (and (20) sub-skills) (reading, writing, operations, computer skills and employability, oral expression and written communication, dialogue, persuasion, influence and arousal, analysis, problem-solving, decision-making, suggestions and hypotheses and employing them. Controlling, directing and balancing, evaluating situations, the skill of cooperating with colleagues and working in study teams, determining information, gathering information, presenting and balancing information) The analysis tool was built (analysis standard) consisting of (80) indicators, and the researchers used the descriptive and analytical approach to achieve the research objectives. The validity and reliability of the analysis tool was confirmed, and the results showed that the skills of cognitive economics are included in the chemistry textbook for the third intermediate grade, but in varying proportions, and that the chemistry textbook For the third grade, he achieved (1029) iterations distributed into six main skills, and that the percentage of availability of knowledge economy skills in the chemistry textbook for the middle grade was ranked in descending order (thinking skills 47%, basic skills 20%, communication skills 17%, information gathering skills 12%, skills Behavioral 3%, teamwork skills 1%) According to these results, it is evident that there is a weakness in the representation of some knowledge economy skills and a variation in the percentages of representation in the content of the chemistry textbook for the third intermediate grade compared to the percentages suggested by the referees and specialists